ANALISIS PERTANGGUNGJAWABAN PIDANA KORPORASI TINDAK PIDANA NARKOTIKA - Sunarto Poniman; Faisal Rusyuandi; Parningotan Malau (Jurnal Hukum to-ra : Hukum untuk mengatur dan melindungi masyarakat, 2026)
Drug-related crimes constitute serious offenses that are not only committed by individuals but also increasingly involve corporations as both instruments and main actors in illegal drug trafficking networks. This study aims to analyze the regulation and implementation of corporate criminal liability in drug-related crimes under Indonesian positive law, as well as to examine the obstacles and possible improvements. This research employs a normative juridical method with statutory, conceptual, and judicial decision analysis approaches. The results reveal that corporations have been recognized as criminal law subjects under Law Number 35 of 2009 on Narcotics; however, technical regulations concerning standards of fault, mechanisms of proof, and corporate punishment remain inadequate. In practice, the enforcement of corporate criminal liability still faces various challenges, including procedural limitations, difficulties in proving corporate intent, limited law enforcement capacity, and structural as well as cultural legal constraints. Therefore, this study recommends strengthening regulatory frameworks, reforming criminal procedural law, enhancing law enforcement capacity, and reinforcing inter-agency coordination to improve the effectiveness of corporate prosecution in narcotics crimes. This research is expected to contribute to the development of national criminal law and to strengthen a more comprehensive and just drug law enforcement system.